Dualism in Our Technoscience: The Influence of Technological Advances and Transhumanism in the Current Anthropological Views in Society, and the Scientific Evidence Behind Them - Lumbreras, Sara (Philosophy, theology and the sciences, 2021)
Western society arguably holds a dualistic view of the human being, with the body being understood as the root of all limitations, including illness and death. This view is shown, more vividly, in most transhumanist positions. The following article presents the sources of this dualism in the technological world, as well as the scientific evidence that points in the opposite direction towards an integral conception of human nature. This includes some specific considerations about the relationship between the body and spirituality. The paper concludes with some examples of technology that could be understood as developed from an integral perspective and could signal an upcoming paradigm shift in this context.